A multiscale view of the Phanerozoic fossil record reveals the three major biotic transitions - Alexis Rojas (Nature Portfolio, 2021)
Rojas et al. present a new multi-scale model that reveals the three major biotic transitions of the Phanerozoic fossil record. This new model supports the hypothesis that both long-term ecological changes and major geological events played crucial roles in shaping ocean mega-assemblages through the Phanerozoic.